Comparing temperature data sources for use in species distribution models: From in‐situ logging to remote sensing - Lembrechts, Jonas Johan; Lenoir, Jonathan; Roth, Nina; Hattab, Tarek; Milbau, Ann; Haider, Sylvia; Pellissier, Loïc; Pauchard, Aníbal; Ratier Backes, Amanda; Dimarco, Romina Daniela; Núñez, Martín Andrés; Aalto, Juha; et al. (Wiley, 2020)
Although species distribution models (SDMs) traditionally link species occurrences to free‐air temperature data at coarse spatio‐temporal resolution, the distribution of organisms might instead be driven by temperatures more proximal to their habitats. Several solutions are currently available, such as downscaled or interpolated coarse‐grained free‐air temperatures, satellite‐measured land surface temperatures (LST) or in‐situ‐measured soil temperatures. A comprehensive comparison of temperature data sources and their performance in SDMs is, however, currently lacking.